Development of fatty liver in children with non-Hodgkin lymphoma - Köse, Doğan; Erol, Cengiz; Kaya, Fatma; Koplay, Mustafa; Köksal, Yavuz (Turkish Journal of Pediatrics, 2014)
The aim of this study is to investigate the development of hepatosteatosis in children with non-Hodgkin lymphoma. Twenty-eight patients were evaluated retrospectively for hepatosteatosis by computed tomography. Mild, moderate and severe hepatosteatosis were defined as the difference between the average liver attenuation and the average spleen attenuation, equaling (- 10) - (- 19); (- 20) - (- 29); and >= 30 HU, respectively. "Vaguely" and "obvious" hepatosteatosis were defined as none or mild hepatosteatosis, and moderate and severe hepatosteatosis, respectively. In T-cell lymphoma, obvious hepatosteatosis was determined in 1 of 12 patients (8.3%) at the first evaluation, 8 of 12 patients (66.7%) at the second evaluation and 4 of 12 patients (33.3%) at the third evaluation. In B-cell lymphoma, obvious hepatosteatosis was determined in none of 16 patients at the first evaluation, 2 of 16 patients (12%) at the second evaluation and none of the patients at the third evaluation. In the second evaluation, severe high serum total cholesterol and triglyceride levels were determined in 4 of 5 patients. We observed higher fatty liver ratios, and high triglyceride and cholesterol levels, although the data were obtained from a small number of patients.
WOS: 000355252900009
PubMed ID: 25818959
Keywords: Children; Fatty Liver; Lymphoma; Non-Hodgkin